Potential Fraud in Student Organizations: A Fraud Hexagon Theory Perspective - Willy Daiva; Dewi Ayu Puspita; Resha Dwi Ayu Pangesti Mulyono (JAFFA, 2024)
Massive fraud in many sectors is still a research topic that is always interesting to study. The Indonesian Corruption Watch report (2023), states that fraud also occurs in the education sector even up to the university level involving students. Students are social control who are role models for society for their knowledge, but it is very contradictory if students also commit fraud in their activities, including in organizational activities. The purpose of this study was to analyze the potential for fraud in the management of student funds using fraud hexagon theory indicators. The research population is students who are members of Student Organizations at the Faculty of Economics and Business, University of Jember. Sample selection using purposive sampling with a sample size of 74 respondents. The results of data analysis show, pressure and capability have a positive effect on the potential fraud of student fund management. While opportunity, rationalization, ego, and collusion have no effect on the potential fraud of student fund management.